The prevalence of episiotomy and associated factors at Shahrara Teaching Hospital in Kabul, Afghanistan - Parvin Golzareh; Sadaf Sultani; Erin M. Mann; Khair Mohammad Mohammadi (BMC Pregnancy and Childbirth)
Abstract Background Episiotomy is done to expand the birth canal but can cause serious complications. It is still commonly performed in many parts of the world representing a quality-of-care and quality-of-life challenge. There is currently no data regarding the prevalence of episiotomy in Afghanistan. The aim of this study was to determine the prevalence of episiotomy and associated factors in women who delivered at a teaching hospital in Kabul, Afghanistan. Methods A retrospective, cross-sectional study was conducted at Shahrara Teaching Hospital. The study sample included all women at Shahrara Teaching Hospital with vaginal delivery during the first six months of 2023. Demographic and clinical information was gathered from medical records. Descriptive statistics were calculated. Logistic regression was performed to assess the independent predictors of episiotomy. Results A total of 1,288 women had vaginal delivery during the study period and 306 (23.76%) delivered using episiotomy. Higher parity was associated with lower odds of episiotomy (OR: 0.01 95% CI 0.007–0.022; p < 0.0001) and a longer duration of labor during stage 2 was associated with higher odds of episiotomy (OR: 1.04 95% CI 1.01–1.07; p = 0.02). An association between Apgar score at the first minute of birth was also associated with higher odds of episiotomy (OR: 1.72 95% CI 0.98–3.03; p = 0.06) although this did not reach statistical significance at a value of p < 0.05. Also of note, the majority of patients received oxytocin (72.2%) and only 1 vacuum delivery was performed representing two additional quality-of-care issues. Conclusions This study is the first to estimate the prevalence of episiotomy in Afghanistan. The rate of episiotomy found in this study was higher than WHO recommendations but lower compared to studies from other low-income or middle-income countries in Asia and Africa. Additional efforts, including national guidelines or policies and workforce training, are needed to further reduce the rate.